Implementasi Permaian Engklek Gunung pada Keterampilan Literasi Numerasi Siswa Kelas 5 Madrasah Ibtidaiyah - Matin, Anas Abdul; Yahya, Fifi Aleyda; Rahayu, Sherli Putri; Wulan, Annisa Nawang; Hermawati, Agustin; Oktaviani, Rizka Nur (FARABI: Jurnal Matematika dan Pendidikan Matematika, 2025)
This research aims to describe the implementation of the mountain crank game in numeracy literacy learning, describe students' numeracy literacy skills after using the mountain crank game media and describe the obstacles of teachers and students who have tried the mountain crank game during numeracy literacy learning for grade 5 students at Madrasah Ibtidaiyah. Numeracy literacy is defined as a basic ability that is essential for children to understand and apply mathematical concepts in everyday life. However, it is often realized that repetitive learning methods can make students less enthusiastic and less focused in learning. This research applies a qualitative method which produces descriptive data in the form of sentences or words based on research findings. The data collection techniques applied are documentation, observation and interviews in this research. Data analysis is carried out interactively with data analysis that is processed in such a way that it appears more complete in the picture. This research shows that the results of the implementation of the mountain engklek game as a learning medium in this class are good, students can understand the material about counting whole numbers in questions which are packaged in the form of numeracy literacy so that many of the students are more interested and active in learning, although some students are still have not been able to understand the material according to the indicators of the material in students' numeracy literacy skills as expected by researchers.